A Barca do Sol: musical banquet (Per Musi, 2018)
Within the context of Brazilian progressive rock groups in the 1970s, A Barca do Sol brings peculiarities that dialogue with the musical scene of those days, and also with the musical production of British groups such as Jethro Tull and Gentle Giant. The preference for using acoustic musical instruments, rhythmic ambiguities and contrapuntal constructions are present in the song Banquete, recorded in 1976, which is examined in this article in the light of recent socio-musicological interpretations - mainly Mathias Lundberg (2014) and Nick Braae (2011) - in order to problematize the relations between the musical elements and the moment in which it was recorded.